Liberal Justice: Teleology and Worldview - Aranda Fraga, Fernando (2019)
The philosophical and economic doctrine of the "Invisible Hand" was formulated by the Scottish philosopher Adam Smith (1723-1790), who is considered one of the greatest exponents of classical economics, as well as the father of political economy. His capital work is The Wealth of Nations. The main thesis of his work is that the key to social welfare lies in economic growth and this is enhanced by an adequate division of labor and competition between free, equal and relatively selfish human beings. Here we analyze how it emerged during Modernity, and even deepening in the last scholastic tracing in Ockham its remote origins, the liberal doctrine of rights and security, in definite accounts, the idea of justice and the worldview that sustains it. In the interregnum of both ages, it is not possible to avoid the convincing fact of the transformation of natural law into positive law and its impact on politics, sociology and economics. This school completes and applies mainly to contemporary economics and social theory with the theoretical outcome on the liberal theory of justice developed by John Rawls, especially between the years 1971-1995. We will dedicate ourselves to these connections and their criticism in what follows.